DIVERSIDADE DO ZOOPLÂNCTON EM TRECHOS DO RIO TRACUNHAÉM LOCALIZADOS EM NAZARÉ DA MATA, PERNAMBUCO, BRASIL - Souza, Sthefany Suellen de; Melo, Laura Leonisa da Silva; Barbosa, Julliany Andrezza da S.; Silva, Manuela K. da; Melo, Viviane Lúcia dos S. Almeida de (Revista Nordestina de Zoologia, 2017)
The objective of the present work was to analyze the composition, richness and structure of the zooplankton community in urban stretches of the Tracunhaém River located in the city of Nazaré da Mata, Pernambuco, Brazil. Monthly collections were carried out between nov/2015 and jul/2016, in two points of study in the coastal region of the river. A total of 19 species (16 for Rotifera and 3 for Crustacea) were recorded. The Rotifera Brachionus bidentata was the most abundant species. Copepoda predominated over Cladocera. It can be concluded that the studied environment show some degree of environmental degradation.